Robot leg for biped walking, phase III - Aclan, Meinard C. (2006)
The trend for mobility has taken over the technological industry. Nowadays, wheeled robots are widely used. But there are certain terrains in which these robots cannot perform the desired tasks. As man aims to mimic himself, bipedal robots are created at various laboratories around the world. This project aims to build a bipedal robot in which the limitations of the previous laboratory projects on biped are addressed. The length of the legs will be designed according to scale with that of a human being. Materials like fiberglass and components such as DC motors, precision potentiometers and motor drivers will be used. The structure will be created from fiberglass material which is lightweight and strong enough to support the robot. Geared DC motors will be used as actuators and precision potentiometers will serve as position and velocity sensors. Organizing the wires will also solve the limitation of hanging wires getting disconnected. A walker will also be provided to support the robot while it is in motion so that damage can be avoided on case of a fall.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Robots -- Control systems; Robots -- Design and construction; Mobile robots; Bipedal robot